The potential health and revenue effects of a tax on sugar sweetened beverages in Zambia. Issue 4 (29th April 2020) - Hangoma, Peter; Bulawayo, Maio; Chewe, Mwimba; Stacey, Nicholas; Downey, Laura; Chalkidou, Kalipso; Hofman, Karen; Kamanga, Mpuma; Kaluba, Anita; Surgey, Gavin
Abstract : The global burden of non-communicable diseases (NCDs) has been rising. A key risk factor for NCDs is obesity, which has been partly linked to consumption of sugar sweetened beverages (SSBs). A tax on SSBs is an attractive control measure to curb the rising trend in NCDs, as it has the potential to reduce consumption of SSBs. However, studies on the potential effects of SSB taxes have been concentrated in high-income countries with limited studies in low-income and middle-income countries. Using data from the 2015 Zambia Living Conditions Monitoring Survey (LCMS) data, the 2017 Zambia NCD STEPS Survey, and key parameters from the literature, we simulated the effect of a 25% SSB tax in Zambia on energy intake and the corresponding change in body mass index (BMI), obesity prevalence, deaths averted, life years gained and revenues generated using a mathematical model developed using Microsoft Excel. We conducted Monte Carlo simulations to construct 95% confidence bands and sensitivity analyses to account for uncertainties in key parameters. We found that a 25% SSB would avert 2526 deaths, though these results were not statistically significant overall. However, when broken down by gender, the tax was found to significantly avert 1133 deaths in women (95% CI 353 to 1970). The tax was found to potentially generate an additional US5.46 million (95% CI 4.66 to 6.14) in revenue annually. We conclude that an SSB tax in Zambia has the potential to significantly decrease the amount of disability-adjusted life years lost to lifestyle-related diseases in women, highlighting important health equity outcomes. Women have higher baseline BMI and therefore are at higher risk for NCDs. In addition, an SSB tax will provide government with additional revenue which if earmarked for health could contribute to healthcare financing in Zambia.